Results of long-term tectonomagnetic research in the Akademik Vernadsky station region, the West Coast of the Antarctic Peninsula - Maksymchuk, V.; Chobotok, I.; Kuderavets, R.; Nakalov, Ye.; Pyrizhok, N.; Pavlyuk, O.; Yanush, L. (Ukrainian Antarctic Journal, 2022)
The study aims to analyze the results of long-term tectonomagnetic observations on the Antarctic tectonomagnetic polygon in the region of the Akademik Vernadsky station to investigate the current geodynamics at the West Coast of the Antarctic Peninsula. The data (1998—2020) were collected as regular discrete geomagnetic measurements. They were used to study the temporal changes of the local magnetic field between the observation epochs and tectonomagnetic anomalies. We create a temporal series of the changes in the local magnetic field for every point of the observation network on the polygon and provide the map of tectonomagnetic anomalies over different observation periods. The tectonomagnetic anomalies of 2.0—2.8 nT · year–1 were found in the Argentine Islands region. The anomalies’ spatial structure agrees with elements of the tectonic structure of the Earth crust. We studied the spatial-temporal connection of the tectonomagnetic anomalies with the region seismicity and estimated the values of tectonic stresses in the lithosphere within the piezomagnetic mechanism. The spatial-temporal structure of tectonomagnetic anomalies in the region shows the response of the geological environment to the change in the tectonic stresses in the local crust. Based on the theoretical calculations and other geological and geophysical data, we conclude that a piezomagnetic effect causes the anomalies under the action of stretching tectonic stresses ( 1 bar · year–1) in the sub-latitudinal direction. Given the urgency of discovering the seismotectonic processes and current regional dynamics, the tectonomagnetic observations on the polygon should be continued as a yearly monitoring program, including other methods of geophysics and geodesy.